Social Media, Cognitive Reflection, and Conspiracy Beliefs - Stecula, Dominik A.; Pickup, Mark (Frontiers in Political Science, 2021)
A growing number of Americans stay informed about current events through social media. But using social media as a source of news is associated with increased likelihood of being misinformed about important topics, such as COVID. The two most popular platforms – Facebook and YouTube – remain relatively understudied in comparison to Twitter, which tends to be used by elites, but less than a quarter of the American public. In this brief research report, we investigate how cognitive reflection can mitigate the potential effects of using Facebook, YouTube and Twitter for news on subsequent conspiracy theory endorsement. To do that, we rely on an original dataset of 1,009 survey responses collected during the first wave of the coronavirus pandemic in the US, on March 31, 2020. We find that using Facebook and YouTube for news increases conspiracy belief (both general and COVID specific), controlling for cognitive reflection, traditional news media use, use of web-based news media, partisanship, education, age, and income. We also find that the impact of Facebook use on conspiracy belief is moderated by cognitive reflection. Facebook use increases conspiracy belief amongst those with low cognitive reflection but has no effect amongst those with moderate levels of cognitive reflection. It might even decrease conspiracy belief amongst those with the highest levels of cognitive reflection.